Evolution of Mechanical Properties and Microstructure in Q&P Processed Unconventional Medium-Carbon Silicon Steel and Comparison between Q&P Processing, Quenching and Tempering, and Austemperingfor - Jenicek, Stepan; Opatova, Katerina; Hajsman, Jan; Vorel, Ivan (Manufacturing Technology Journal, 2022)
The quenching and partitioning (Q&P) process is an advanced method of heat treatment of high-strength steels. The resulting properties of Q&P-processed steels are dictated by their microstructure which consists of tempered martensite, fresh martensite and retained austenite (RA). These phases arise from individual steps of the Q&P-process. An important step is stabilization of retained austen-ite because RA raises ductility to above the levels found in conventional steels upon quenching and tempering. If the desired stability of RA is to be achieved, Q&P processing must not initiate compet-ing processes associated with carbide precipitation or austenite decomposition into bainite-like mi-crostructure. Yet, it appears that the very decomposition of austenite into bainite is an accompanying process that takes place at the partitioning stage, the stage which plays an important role in terms of mechanical properties of Q&P-processed steels.
Keywords: Q&P process; Bainite; Martensite; Mechanical properties